Peran Pterostilbene Stilbene Sebagai Agen Anti Kanker - Laily Septia Andini (Jurnal Riset Ilmu Kesehatan Umum dan Farmasi (JRIKUF), 2025)
Cancer is a group of diseases characterized by uncontrolled cell growth, invasion of surrounding tissue, and potential spread to other parts of the body through a process called metastasis. Cancer can occur in almost any organ or body tissue, such as the lungs, skin, colon, pancreas, and others. The cause of cancer is multifactorial, involving genetic factors, the environment, lifestyle and certain infections. Pterostilbene is a phytochemical compound belonging to the stilbenoid group, found mainly in blueberries and grapes. These phytochemicals have demonstrated significant therapeutic potential in the context of cancer prevention and treatment. Various preclinical and clinical studies have identified pterostilbene's broad anti-cancer activities, including induction of apoptosis (programmed cell death), inhibition of cancer cell proliferation, and inhibition of metastasis (the spread of cancer cells to other parts of the body).Pterostilbene's mechanism of action involves the modulation of various molecular pathways. , such as the NF-κB, PI3K/Akt, and p53 pathways, which play important roles in cell cycle regulation, apoptosis, and cellular stress responses. Additionally, pterostilbene also has strong antioxidant properties, which can protect cells from oxidative damage that often contributes to the development of cancer